A Hauntology of Clandestine Transmissions: Spectres of Gender and Race in Electronic Music. (October 2022) - Gray, Chantelle
Electronic music is often presented as originating with the Futurists, John Cage, Robert Moog, Kraftwerk and the Detroit techno scene, yet such descriptions elide the role of women in the history of electronic and experimental music and, importantly, occlude contributions from non-western and non-white musicians. This clandestine history is further obscured by the fact that although there are as many women artists working within electronic and experimental music as there are men, men continue to dominate related events and festivals. In this article, I use Jacques Derrida's notion of hauntology—a portmanteau of 'haunting' and 'ontology'—to frame such practices of historiography. For Derrida, hauntology marks not a belief in ghosts but, rather, an ethical injunction to preserve otherness, even while such otherness may not be wholly comprehensible to us. The aim of this article is thus twofold: first, to provide a contextualisation of hauntology; and second, to produce a spectrography of electronic and experimental music, of occluded histories and their haunting presence/absence coordinates, in order that we might remember—sit with—the forgotten h(er)istories while all the time acknowledging that these tellings are themselves necessarily partial.